Morphological characterization of the Rembi sheep population in the Tiaret area (West of Algeria) - DJAOUT, A; AFRI-BOUZEBDA, F; BOUZEBDA, Z; ROUTEL, D; BENIDIR, M; BELKHIRI, Y (The Indian Journal of Animal Sciences, 2015)
Morphological characterization of Rembi breed was carried out from the study of 3 representative herds. Ewes (41) and rams (13) with an average age of 4.30 ± 1.48 years were recorded for their live weight and 21 morphological measures with qualitative characters. Differences between sexes were revealed for several measures, whereas no differences were revealed between regions. A factorial analysis of multiple correspondences was performed on the morphological measures and revealed two main principal components accounting for 36.85 and 18.63 % of the inertia, being related to the color of the head (face and neck), neck and legs, the presence and absence of horns and sex. The cluster analysis allowed establishing differences with relevant implications to be taken into account for the breed conservation programme.